Online shopping trend and trust during Covid-19 movement control order - Khairunesa Isa; Jurry Foo; Sarala Thulasi Palpanadan; Fadzlunesa Isa (Pennwell Corporation, 2020)
The spread of Covid-19 pandemic has shown an increase from January 2020. The situation resulted in Movement Control Order (MCO) that has been implemented in the first stage, beginning from 18th to 31st of March 2020. During this MCO, most of the sales and purchase activities were carried out online. Booking order for online merchandise increased dramatically and some of them had to stop the booking due to insufficient supply. Therefore, this study tries to identify the trend and trust towards online purchase among consumers during MCO due to Covid-19 pandemic. This survey was distributed using Google Form and involved 280 respondents from all over Malaysia. The findings showed that respondents already knew about and were involved in online purchase since the services was introduced in Malaysia. The implementation of MCO only affected a small number only. Meanwhile, most of the respondents tend to choose online purchase because of the advantages and they put their trust to purchase online because the service after sale really satisfied them.